Para o bem de Roma: Creúsa e Lavínia na Eneida - Pereira, Virgínia Soares (2012)
The modem studies on the Classical Antiquity highlight focus on the generalized interest for the question of woman’s representation and Aeneid was not forgotten in this general trend. Not only do the approaches related to the role of the female figure multiply but they also contribute to the understanding of the symbolical and the political significance of the poem. Confining itself to only two apparently somewhat irrelevant figures in the narrative plot, this present work aims to reflect on the role attributed by Vergil to Creusa and Lavinia, Eneias’ two wives.